2011
DOI: 10.1096/fj.11-183822
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral glucose and lactate consumption during cerebral activation by physical activity in humans

Abstract: At rest, the brain takes up oxygen and carbohydrate at an ~6:1 ratio. Exercise increases systemic lactate availability reducing this to as little as 1.7:1 despite a ~20% increase in cerebral metabolic rate for oxygen (CMRo₂), thus indicating a disproportionate increase of carbohydrate metabolism. Underlining mechanisms and metabolic fate for the augmented lactate uptake are unknown. This meta-analysis examines whether adrenergic activation explains the increased lactate uptake, cerebral lactate release followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 72 publications
4
64
0
Order By: Relevance
“…Basal lactate uptake into the brain in our study at euglycemia (V in , 0.14 μmol/min/g at plasma level 2-3 mM) is consistent with several other studies that have measured this parameter in the context of rest and exercise in healthy subjects, as summarized by Rasmussen et al (35). In this study, we found that one of the adaptations to recurrent hypoglycemia was a significant enhancement of lactate uptake (V in , 0.26 μmol/g/min) into the brain under hypoglycemia ( Figure 4A).…”
Section: Discussionsupporting
confidence: 92%
“…Basal lactate uptake into the brain in our study at euglycemia (V in , 0.14 μmol/min/g at plasma level 2-3 mM) is consistent with several other studies that have measured this parameter in the context of rest and exercise in healthy subjects, as summarized by Rasmussen et al (35). In this study, we found that one of the adaptations to recurrent hypoglycemia was a significant enhancement of lactate uptake (V in , 0.26 μmol/g/min) into the brain under hypoglycemia ( Figure 4A).…”
Section: Discussionsupporting
confidence: 92%
“…Locus coeruleus stimulation increases brain vascular water permeability and an ␣-adrenergic blocker reduces water permeability [56], whereas increased water permeability during seizures was unaffected by unilateral locus coeruleus lesion [25]. However, water derived from blood is considered insufficient to support perivascular metabolite clearance because hemoglobin levels across brain do not change during exercise [57]. Given the large flow differences for blood and perivascular-lymphatic flow (in rats: ∼1 mL/min/g blood flow vs. ∼0.3 L/g/min perivascular flow [5]; Note: the latter rate approximates calculated production of metabolic water from glucose oxidation, without including CSF clearance), even a small diversion of water from blood could have a high impact on lymphatic drainage.…”
Section: Astrocytic Contributions To Ogi: Lactate Release To Blood Anmentioning
confidence: 99%
“…This fuel monodependence has been explained by the inability of albumin-bound fatty acids to cross the blood -brain barrier and the fact that ATP production requires less oxygen from glucose than from fat. Minor substrates, like lactate and ketone bodies, may become significant if their blood levels are elevated, as occurs in strenuous exercise or when fasting (Dalsgaard et al 2004;Yellen 2008;Rasmussen et al 2011). Glucose enters the brain via the endothelial transporter GLUT1 and is then captured by astrocytic endfeet, which are also rich in GLUT1 (Kacem et al 1998).…”
Section: Energy Uptake Storage and Deliverymentioning
confidence: 99%